The Relationship Of Anxiety Levels With The Event Of Dysmenorrhea In Napsi'ah Private Vocational School Students, Stabat Kab. Langkat Year 2022 - Siskawati Amri; Nanarita Tarigan; Siti Saodah; Nurhasanah (Science Midwifery, 2022)
The purpose of this study was to determine the relationship between anxiety levels and the incidence of dysmenorrhea in private vocational high school students Napsi'ah Stabat kab. Langkat in 2022. The research method used is a cross-sectional study design. The research objective is to determine the relationship between anxiety levels and the incidence of dysmenorrhea in female students.The sampling technique used was total sampling, namely the sampling technique based on the entire population. So the number of samples in this study were 30 people. Based on the results of research and discussion of the relationship between anxiety levels and the incidence of dysmenorrhea in private vocational school students Napsi'ah Stabat kab. Langkat in 2021 with a total of 30 respondents. The level of anxiety in private vocational school students Napsi'ah Stabat kab. In 2021, out of 30 respondents, the majority of mild anxiety were 12 people (40.0%). The incidence of dysmenorrhea in private vocational school students Napsi'ah Stabat kab. In 2021, out of 30 respondents, the majority did not occur, amounting to 17 people (56.7%). There is a relationship between the level of anxiety on the incidence of dysmenorrhoea in private vocational school students Napsi'ah Stabat kab. Langkat.